Partial characterisation of citrus mosaic virus - Y.S. AHLAWAT, R.P. PANT and (Indian Phytopathology, 2002)
Citrus mosaic disease is of common occurrence in Andhra Pradesh, India. A bacilliform virus belonging to the badnavirus group was associated with the mosaic disease. The virus was transmitted by wedge grafting and mechanical inoculations from citrusto citrus but not by 3 species of Pseudococcidae and Aphidoidea. Out of 15 cultivars inoculated with the virus, 14 were infected. The particles associated with citrus mosaic are non-enveloped bacilliform, measuring 125-130X25-30 nm in size. The virus was serologically related to sugarcane bacilliform badnavirus (ScBV) and 8 other badnaviruses. A polyclonal antiserum was developed and used to detect the virus in 7 ELISA and immunosorbent electron microscopy (IEM) assays.